STUDI KOHESI LEKSIKAL DALAM BAHASA ARAB: TINJAUAN HIPONIMI DAN KOLOKASI DALAM AL-QUR’AN - Abd Aziz (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2024)
Lexical cohesion plays an important role in building the integration and unity of a text, so that the meaning conveyed can be understood clearly and systematically. This study aims to analyze lexical cohesion in the discourse of the Qur'an by focusing on two main aspects, namely hyponymy and collocation. Hyponymy refers to the hierarchical relationship between more specific words and more general words, while collocation refers to the tendency of certain words to often appear with other words in a context. The research method used in this study is qualitative descriptive analysis with a discourse linguistics approach. The research data were taken from the verses of the Qur'an that show the relationship between hyponymy and collocation. Data collection techniques were carried out through literature studies and documentation, while data analysis used a semantic approach to identify patterns of meaning relationships between words. The results of the study show that hyponymy in the Qur'an is often used to organize concepts in a clearer hierarchical structure, such as the classification of types of animals, plants, and food. Meanwhile, collocation in the Qur'an forms a consistent pattern, reflecting the constancy of meaning that strengthens the cohesion of the text. The use of lexical cohesion not only enriches the language structure in the Qur'an, but also supports a deeper understanding of meaning for its readers. Thus, this study confirms that lexical cohesion is an essential aspect in building discourse integration, especially in religious texts that have complex language structures